2019
DOI: 10.1101/600106
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Tumor-targeted delivery of childhood vaccine recall antigens by attenuatedListeriareduces pancreatic cancer

Abstract: Pancreatic ductal adenocarcinoma is poorly immunogenic, and immune suppression prevents T cell activation. We developed a microbial-based immunotherapeutic concept for selective delivery of immunogenic tetanus toxoid (TT856-1313) antigen into tumor cells by attenuated Listeria monocytogenes, and reactivation of TT-specific memory T cells to kill infected tumor cells. Treatment of KPC mice with Listeria-TT resulted in TT accumulation inside tumor cells, and attraction of TT-specific CD4 and CD8 T cells.Lymph no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(18 citation statements)
references
References 82 publications
(162 reference statements)
1
17
0
Order By: Relevance
“…The MDSC population was also reduced in tumors of the NAM+GEM group, although this was not statistically significant because of high variability in the saline treated mice (Fig 2c). However, the MDSC population in blood was reduced by GEM alone (p<0.05) (Fig 2d), supporting our results in a previous study 16 .…”
Section: Nam+gem Increases the Influx Of Immune Cells And Activates Tsupporting
confidence: 91%
See 4 more Smart Citations
“…The MDSC population was also reduced in tumors of the NAM+GEM group, although this was not statistically significant because of high variability in the saline treated mice (Fig 2c). However, the MDSC population in blood was reduced by GEM alone (p<0.05) (Fig 2d), supporting our results in a previous study 16 .…”
Section: Nam+gem Increases the Influx Of Immune Cells And Activates Tsupporting
confidence: 91%
“…Ccl21a was also increased in the NAM or GEM groups but less robust than in NAM+GEM. In another study, we also found that GEM improved the migration of T cells to pancreatic tumors 16 . Finally, we found a 4-fold reduction in Lcn-2 and a less robust but still significant reduction in Muc-1 and Epcam.…”
Section: Immuno-oncology Gene Expression Profiling Shows Enhanced Immmentioning
confidence: 70%
See 3 more Smart Citations